Prognostic factors in gastric cancer patients: a 10-year mono-institutional experience - De Ruvo, N.; Fenocchi, S.; Veronesi, L.; Missori, G.; Ricciardolo, A. A.; Rossi, E. G.; Sorrentino, L.; Cautero, N.; Serra, F.; Gelmini, R. (Frontiers in Surgery, 2024)
Gastric cancer (GC) is one of the leading main causes of death for cancer worldwide, long-term survival remains dismal above all in Western Countries, with no significant improvements in recent years. Therefore a correct identification of clinical-pathological risk factors is crucial for prognosis, as it allows a better selection of patients suitable to oncologically radical treatments and longer survivals.We devised a retrospective observational longitudinal study over a 10 years experience with GC patients operated with curative intent.Several factors were thoroughly investigated in a multivariate analysis to look for significance as indipendent risk factors for DFS. Our results show that only BMI, pTNM and LNR, in our series of patients, expressed hazard ratios for survival.Although limited by the retrospective nature of the study, this is one of the few Northern Italy cancer reports, showing results over a 10 years period, which might in our view have an impact on decisionmaking processes for those multidisciplinary teams dedicated to the care of gastric cancer patients.